The Impact of Learning Independence on Self-Efficacy and Academic Success of Elementary Students in West Papua - Suherman; Harsono; Widiyasari, Choiriyah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the impact of learning independence on self-efficacy and academic success among elementary students in West Papua, within an educational context characterized by limited resources and external support. A quantitative approach with a census sampling method was employed, involving 85 students. Data were collected using questionnaires on self-efficacy and learning independence, and multiple regression analysis was applied to assess the relationships between these variables and academic success. The results revealed that both self-efficacy and learning independence significantly contribute to academic success, with each factor mutually reinforcing the other to enhance student learning outcomes. In conclusion, educational programs aimed at improving self-efficacy and learning independence can significantly boost academic performance, particularly in resource-constrained environments. The study also highlights the potential of project-based learning and collaborative activities to increase student engagement and deepen their understanding of complex concepts. Educators can further support students by providing constructive feedback and emotional encouragement, fostering an environment that empowers students to overcome challenges and achieve their full potential. This study suggests the development of community-based educational interventions that focus on these factors to improve the overall quality of education.